Interesterificação de óleo de soja para produção de ésteres metílicos de ácidos graxos catalisada por óxido de cálcio - Nunes, Ana Luiza Barrachini (2018)
Price instability of fossil fuels and search for renewable energies have stimulated government programs to increase the percentage of biodiesel in diesel. This biofuel is generally produced by the transesterification reaction, however the various stages of purification to obtain a clean biodiesel, glycerin market saturation and the effluents generated demand the study of new routes for this biofuel production. This study evaluated heterogeneous interesterification from soybean oil and methyl acetate, catalyzed by calcium oxide. Catalyst obtained from calcium carbonate was tested in the reaction after different calcination temperatures, and the hydration-dehydration technique was used to produce nanocrystalline catalyst. CaO samples were characterized by X-ray diffraction, thermogravimetric analysis, Fourier transform infrared spectroscopy, scanning electron microscopy and N2-physisorption at 77K. Interesterification reaction at 275 °C, 1:40 molar ratio oil: methyl acetate and 6 wt% catalyst content for 120 minutes was used with Tukey's test to determine the best calcination temperature, equal to 800 °C. Selected catalyst was used in kinetic experiments to evaluate the effect of temperature, catalyst concentration and oil: methyl acetate molar ratio. The optimum condition was 325 °C, catalyst content of 10 wt%, and 1:40 oil: methyl acetate molar ratio, with a 62.3 wt% fatty acid methyl esters content. Reuse catalyst was tested and the results showed a decreasing catalytic activity. Leaching test and FTIR analysis of the catalyst pointed out to mass loss and adsorbents at the basic sites would be contributing to CaO deactivation.